2011
DOI: 10.1590/s0104-11692011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexually transmitted diseases in female sex workers in a city in the interior of São Paulo, Brazil

Abstract: Changes in the profile of sexually transmitted diseases have increased the need for their detection, particularly where there is a concentration of individuals with risk behavior, so that diagnosis and immediate treatment can be translated in the reduction of resulting problems. The objective was to identify the prevalence of sexually transmitted diseases in female sex workers in a medium-sized city in São Paulo state. This population prevalence study was conducted in 2008 on 102 females. The prevalence was 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
4
0
3
Order By: Relevance
“…The high prevalence of syphilis among FSWs has been reported in lowincome countries, such as the Dominican Republic (5.1-11.1%), Honduras (1.3-6.0%), Guatemala (1.1-11.8%), El Salvador (2.7-15.0%) and Peru (2.2-4.1%) [15]. The prevalence of syphilis was high (14.1%), which was 65% higher than a recent study that evaluated a similar population of FSWs from 12 Brazilian cities (8.5%) [16], and 3.5 higher than the prevalence found in the city of Botucatu (4%), southeast Brazil [17] using rapid qualitative test and ELISA. These results indicate the disparity on syphilis prevalence among FSWs in Brazil, as well as the need for syphilis control and preventive measures in marginalized populations, such as the observed in this Amazon region and other populations worldwide.…”
Section: Discussionmentioning
confidence: 58%
“…The high prevalence of syphilis among FSWs has been reported in lowincome countries, such as the Dominican Republic (5.1-11.1%), Honduras (1.3-6.0%), Guatemala (1.1-11.8%), El Salvador (2.7-15.0%) and Peru (2.2-4.1%) [15]. The prevalence of syphilis was high (14.1%), which was 65% higher than a recent study that evaluated a similar population of FSWs from 12 Brazilian cities (8.5%) [16], and 3.5 higher than the prevalence found in the city of Botucatu (4%), southeast Brazil [17] using rapid qualitative test and ELISA. These results indicate the disparity on syphilis prevalence among FSWs in Brazil, as well as the need for syphilis control and preventive measures in marginalized populations, such as the observed in this Amazon region and other populations worldwide.…”
Section: Discussionmentioning
confidence: 58%
“…The prevalence of T. vaginalis in each age group depends on several factors, including the technique used to assess this prevalence [17][18][19][20]. For example, research using culture, wet mount, and Pap smear found a prevalence of 2.6% in women attending primary health clinics in Uberlândia, MG, in the southeast region of Brazil [18].…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, a prevalência de sífilis encontrada em MPS, nessa revisão integrativa, os dados mostraram a alta prevalência dessa infecção em diferentes países: europeus, asiáticos e latino americanos (1-2-3) . Vale desatacar que um estudo realizado no Brasil com 102 MPS encontrou prevalência de 4,0% de sífilis em MPS (20) .…”
Section: Medidas Interventivasunclassified
“…A presença de infecções por sífilis, também, pode estar associada a outras infecções como clamídia 7% e gonorréia 3,5% em 7500 MPS na China (4) . Pesquisa nacional realizada no sudeste do país, mostrou que 102 MPS obtiveram uma prevalência de IST de 71,6%, sendo que os maiores valores encontrados foram para o HPV 67,7% e infecção clamidiana 20,5% (20) . Esses achados mostram que práticas de risco aumentam a vulnerabilidade aos diversos agravos.…”
Section: Medidas Interventivasunclassified